Analysis of the Effect of the Use of Environmentally Friendly Building Materials on the Stability of Tall Building Structures in Jakarta - Heka Ardana, Putu Doddy; Arini, Rani Eka; Priyana, Yana (Westscience Press, 2024)
The construction industry's significant environmental impact has prompted a shift towards environmentally friendly building materials to mitigate environmental degradation while maintaining structural stability. This quantitative study investigates the effect of using environmentally friendly building materials on the stability of tall building structures in Jakarta, Indonesia. Employing a mixed-methods approach, survey data collection, and structural analysis techniques were utilized to examine the relationship between building material choices and structural stability. Statistical analyses revealed a strong preference for environmentally friendly materials among participants, with sustainable timber and eco-friendly concrete substitutes receiving high ratings. Moreover, participants expressed confidence in the structural integrity of tall buildings constructed using these materials. Correlation and regression analyses further demonstrated significant positive relationships between preferences for environmentally friendly building materials, perceived structural stability, and environmental sustainability practices. The findings underscore the potential of environmentally friendly building materials to enhance both structural stability and environmental sustainability in tall building construction.